PERAN UMKM (USAHA MIKRO KECIL MENENGAH) DALAM MENINGKATKAN KESEJAHTERAAN MASYARAKAT DI KELUTAHAN SUMBER REJO KECAAMATAN BALIKPAPAN TENGAH - Didik Hadiyatno; Misna Ariani; Tutik Yuliani (Jurnal Abdimas Bina Bangsa, 2023)
MSMEs play an important role as a potential sector and maintaining economic stability. In general, considering that small and medium businesses have a very high involvement in the workforce and improving people's welfare. MSMEs are known as an acronym for Micro, Small, Medium Enterprises. However, if we look at it from different definitions and points of view, MSMEs have a much broader meaning. For business actors, MSMEs are businesses or businesses run by individuals, households or small business entities